Fungicide systemicity and blast control in wheat heads - Daniela da Silva; Marcos Kovaleski; Cláudia Cristina Clebsch; Mateus Mossolin; Carolina Cardoso Deuner; João Leodato Nunes Maciel (Semina: Ciências Agrárias)
The chemical control of wheat blast, a disease caused by Pyricularia oryzae Triticum (PoT), is part of the integrated management of this disease. The aim of this study was to evaluate fungicide systemicity in wheat heads and its effect on blast control. BRS 264 cultivars were grown in pots until anthesis (Zadoks stage 65), after which two central spikelets were removed from each head, exposing the rachis, where fungicide solutions were applied. Seven fungicides were evaluated (Flutriafol, Tebuconazole, Propiconazole, Pydiflumetofen, Cyproconazole, Pyraclostrobin and Mancozeb), as well as the control treatment with no fungicides and only water applied. Twenty-four hours after the solution was applied, a conidial suspension (105 conidia mL-1) of PoT was sprayed on the heads and the plants were kept at 24 ºC, 90-95% relative humidity (RH) and in the dark for a further 24 hours. They were then kept at 24 ºC, 70-80% RH under a 12-hour photoperiod until disease severity on the heads was assessed 5, 7 and 11 days after inoculation (dai). Between 20 and 30 heads were evaluated per treatment. Severity above and below the treated area was assessed by the generalized beta regression model. Above the treated area, at 5 and 7 days, the treatments with Flutriafol, Tebuconazole, Propiconazole, Pydiflumetofen and Cyproconazole differed from Check, showing lower average blast severity. Mancozeb and Pyraclostrobin also showed lower disease severity compared to the Check treatment when the overall results were analyzed. The acropetal movement of fungicides should be considered along with other approaches to integrated wheat blast management.